1993
DOI: 10.1111/j.1440-1827.1993.tb03233.x
|View full text |Cite
|
Sign up to set email alerts
|

Epstein‐Barr virus related gastric cancer in Japan: A molecular patho‐epidemiological study

Abstract: Epstein‐Barr virus (EBV) involvement in gastric carcinoma has been demonstrated by the presence of EBV genomes and EBV‐encoded small RNA (EBER) in the carcinoma cells, monoclonal proliferation of EBV‐infected carcinoma cells and elevated antibody titers. The present study was conducted to investigate the prevalence of EBV involvement among gastric carcinomas observed in nine Japanese cities with varying gastric cancer rates. In situ hybridization of EBER‐1 was applied to paraffin sections from 1848 carcinomas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
77
2

Year Published

1996
1996
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(85 citation statements)
references
References 13 publications
(2 reference statements)
5
77
2
Order By: Relevance
“…41 Male predominance was one of the most evident clinicopathologic features of EBV-associated GC demonstrated in previous studies. 10,11,16,40 Although we also found male predominance in the present study, the gender ratio (male/female) was merely 1.9, which did not achieve statistical significance, and was lower than the gender ratios reported elsewhere. Although most of the studies reported so far showed male predominance, a notable exception is the finding reported in Mexico by Herrera-Goepfert et al 41 In that study the male/female ratio was 1.1.…”
Section: Factors Associated With Ebv Positive Casescontrasting
confidence: 99%
See 1 more Smart Citation
“…41 Male predominance was one of the most evident clinicopathologic features of EBV-associated GC demonstrated in previous studies. 10,11,16,40 Although we also found male predominance in the present study, the gender ratio (male/female) was merely 1.9, which did not achieve statistical significance, and was lower than the gender ratios reported elsewhere. Although most of the studies reported so far showed male predominance, a notable exception is the finding reported in Mexico by Herrera-Goepfert et al 41 In that study the male/female ratio was 1.1.…”
Section: Factors Associated With Ebv Positive Casescontrasting
confidence: 99%
“…25,[35][36][37][38][39] Our frequency of 16.8% of EBV-positive tumors is contrary to a previously proposed hypothesis that high-risk countries for GC have low rates of EBV-associated GC. 40 For example Japan, a country with a high prevalence of GC, studies have shown an association between EBV and GC of 6.7%. 11 Conversely, in the U.S., a country with a low prevalence of GC, studies have shown an association of 16%.…”
Section: Factors Associated With Ebv Positive Casesmentioning
confidence: 99%
“…Meanwhile, we have applied this screening method to an additional 82 randomly selected cases, and observed an overall EBV positivity of 7.7% in a total of 324 cases from 19 different Dutch hospitals (data not shown). This is in agreement with the current literature concerning the prevalence of EBV-carrying gastric adenocarcinomas worldwide (7,9,29,30).…”
Section: Discussionsupporting
confidence: 82%
“…Although MI was noted in a high percentage of gastric cancers with a positive family history (Akiyama et al, 1996;Keller et al, 1996;Ottini et al, 1997), germline or somatic mutations of the mismatch repetition and repair (MMR) genes were rarely reported (Akiyama et al, 1996;Keller et al, 1996). Thus, the mechanism leading to the mismatch repair failure in gastric carcinomas remains largely unknown.The association between EpsteinÐBarr virus (EBV) and gastric cancer also varies among different populations, with the highest positive association occurring in Caucasian populations (Shibata and Weiss, 1992;Ott et al, 1994) and a low association seen in the Japanese (Tokunaga et al, 1993). EBV is found in more than 80% of a specific histological variant of gastric carcinoma, variably termed lymphoepithelioma-like carcinoma (LELC), medullary or gastric carcinoma with lymphoid stroma (Nakamura et al, 1994).…”
mentioning
confidence: 99%
“…The association between EpsteinÐBarr virus (EBV) and gastric cancer also varies among different populations, with the highest positive association occurring in Caucasian populations (Shibata and Weiss, 1992;Ott et al, 1994) and a low association seen in the Japanese (Tokunaga et al, 1993). EBV is found in more than 80% of a specific histological variant of gastric carcinoma, variably termed lymphoepithelioma-like carcinoma (LELC), medullary or gastric carcinoma with lymphoid stroma (Nakamura et al, 1994).…”
mentioning
confidence: 99%